ANALISA PENDAPATAN PETERNAKAN AYAM KAMPUNG DI DESA PAYUNGAN KECAMATAN KALIWUNGU KABUPATEN SEMARANG - Muh Samsudin; Arif Nugroho Rachman (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
This study aims to determine the amount of income generated from native chicken farming businesses in Payungan Village, Kaliwungu District, Semarang Regency, as well as the factors that influence the income of native chicken farmers in the same area. The research employs a quantitative approach, using the formula of total revenue minus total costs, and analyzes the ratio between production output and the expenses incurred by the farmers in Payungan Village, Kaliwungu District, Semarang Regency. The population is considered unlimited, so the researcher applied a random sampling technique with predetermined criteria. A total of 30 respondents were selected from Payungan Village, Kaliwungu District, Semarang Regency. The data processing and analysis revealed that the average income from native chicken farming in Payungan Village, Kaliwungu District, Semarang Regency is Rp. 5,080,000. The factors influencing household income from native chicken farming include fluctuations in market prices and the quantity of chickens sold or harvested. Based on the analysis of the production-to-cost ratio, the study concludes that household native chicken farming in Payungan Village, Kaliwungu District, Semarang Regency is feasible and worth continuing.